Partial Characterization of a Novel Reovirus Isolated from a Hypovirulent Strain (9B21) of Cryphonectria parasitica (Murrill) Barr - SUPYANI SUPYANI (Society for Indonesian Biodiversity, 2009)
A filamentous fungus Cryphonectria parasitica (Murrill) Barr. is the causal agent of the chestnut blight disease. This fungus has some hypovirulent strains. These strains are known to be infected by viruses. To date, many species of viruses havebeen found to be associated with C. parasitica strains. The number genome segments, their relative size, titer and sequence homology as well as the effects on host fungal virulence and morphology were varied among the C. parasiticaassociating viruses. Cryphonectria parasitica mycoreovirus-1 (CpMYRV1) is a newly characterized reovirus isolated from C.parasitica. The viral genome consists of 11 segments of dsRNA termed S1 to S11. The aims of this research were to determine the complete sequences of the three shortest segments (S9-S11) of CpMYRV1, and to analyze the relationship of the dsRNA segments to the segments within the reoviruses genome. Sequence analyses showed that segments S9, S10, and S11 are 1072 bp, 975 bp, and 732 bp in size with single ORFs coding for 297, 247, and 101 amino acids respectively. Genome segments S9 to S11 have common terminal sequences, 5â€™GAUCA— GCAGUCA3â€™. The deduced amino acid sequence coded by segment 9 showed a similarity to P11 of evolutionarily related Rosellinia anti-rot virus (Reoviridae), while S10 or S11 exhibited they were no significant sequence similarities to the known sequences published.Key words: Cryphonectria parasitica, CpMYRV1, molecular characterization.